2022
DOI: 10.31234/osf.io/kwf4r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A review of the anatomy and function of the white matter tracts in language production and comprehension

Abstract: Much is known about the role of various cortical areas in language production and comprehension. The shift towards network approaches in recent years has highlighted the importance of uncovering the role of the white matter in connecting these areas. However, despite a relatively large body of research, the function of many of these tracts is still underdefined. In this paper, we present a comprehensive review of the empirical evidence on the role of eight major tracts that are hypothesized to be involved in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 380 publications
2
2
0
Order By: Relevance
“…In line with this hypothesis, Budisavljević et al (2017) showed an association between the microstructural properties of the bilateral FAT and the hand kinematics in the grasping and reaching-to grasp movements, performed with the right hand. This proposal aligns well with the hypothesis that the FAT is primarily involved in the selection and control of the appropriate plan for motor action, consistently with what suggested by recent literature about the role of this tract (Dick et al, 2019; Shekari & Nozari, 2022). The fact that in BBs the inhibition of the signed modality involves both the right and the left FAT, while the inhibition of the spoken modality only involves the left FAT, further supports the idea that, on the left side, the FAT specializes for the control of speech actions (Dick et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with this hypothesis, Budisavljević et al (2017) showed an association between the microstructural properties of the bilateral FAT and the hand kinematics in the grasping and reaching-to grasp movements, performed with the right hand. This proposal aligns well with the hypothesis that the FAT is primarily involved in the selection and control of the appropriate plan for motor action, consistently with what suggested by recent literature about the role of this tract (Dick et al, 2019; Shekari & Nozari, 2022). The fact that in BBs the inhibition of the signed modality involves both the right and the left FAT, while the inhibition of the spoken modality only involves the left FAT, further supports the idea that, on the left side, the FAT specializes for the control of speech actions (Dick et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…All this evidence is consistent with the proposal that the FAT is involved in inhibitory control processes, also for those related to the regulation of the output of speech (Shekari & Nozari, 2022). However, the exact role of the FAT and whether its function is mainly related to domain-general or language-specific processes has not been fully understood.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations